Hyaluronan-conjugated liposomes encapsulating gemcitabine for breast cancer stem cells - Han NK (International Journal of Nanomedicine, 2016)
Na-Kyung Han,1,* Dae Hwan Shin,1,* Jung Seok Kim,1 Kwon Yeon Weon,2 Chang-Young Jang,1 Jin-Seok Kim1 1Research Center for Cell Fate Control (RCCFC) and College of Pharmacy, Sookmyung Women’s University, Seoul, 2College of Pharmacy, Catholic University of Daegu, Gyeongbuk, Korea *These authors contributed equally to this work Abstract: Investigation of potential therapeutics for targeting breast cancer stem cells (BCSCs) is important because these cells are regarded as culprit of breast cancer relapse. Accomplishing this kind of strategy requires a specific drug-delivery system using the distinct features of liposomes. Studies on targeted liposomal delivery systems have indicated the conjugation of hyaluronan (HA), a primary ligand for CD44 surface markers, as an appropriate method for targeting BCSCs. For this study, enriched BCSCs were obtained by culturing MCF-7 breast cancer cells in nonadherent conditions. The enriched BCSCs were challenged with HA-conjugated liposomes encapsulating gemcitabine (2, 2-difluoro-2-deoxycytidine, GEM). In vitro study showed that the HA-conjugated liposomes significantly enhanced the cytotoxicity, anti-migration, and anti-colony formation abilities of GEM through targeting of CD44 expressed on BCSCs. In pharmacokinetic study, area under the drug concentration vs time curve (AUC) of the immunoliposomal GEM was 3.5 times higher than that of free GEM, indicating that the HA-conjugated liposomes enhanced the stability of GEM in the bloodstream and therefore prolonged its half-life time. The antitumor effect of the immunoliposomal GEM was 3.3 times higher than that of free GEM in a xenograft mouse model, probably reflecting the unique targeting of the CD44 receptor by HA and the increased cytotoxicity and stability through the liposomal formulation. Furthermore, marginal change in body weight demonstrated that the use of liposomes considerably reduced the systemic toxicity of GEM on normal healthy cells. Taken together, this study demonstrates that HA-conjugated liposomes encapsulating GEM show promise for the therapy of breast cancer in vitro and in a xenograft model by targeting the BCSCs. Keywords: breast cancer stem cells, targeting, CD44 surface marker, EPR effect, drug delivery system